Does a Care Bundle Reduce Racial Disparities in Postcesarean Surgical Site Infections? - Kawakita, Tetsuya; Umans, Jason G. (American Journal of Perinatology, 2019)
Objective To examine the effect of a care bundle on racial disparities in surgical site infections (SSIs).Study Design This was a retrospective cohort study of women undergoing cesarean delivery at ≥23 weeks' gestation. The care bundle included routine antibiotics (both cefazolin and azithromycin), chlorhexidine skin preparation, clippers, vaginal cleansing, placental removal by cord traction, subcutaneous tissue closure, suture skin closure, dressing removal in 24 to 48 hours, and postoperative chlorhexidine soap. Our primary outcome was SSI (superficial incisional, deep incisional, and organ/space) occurring up to 6 weeks. Adjusted odds ratios (aOR) with 95% confidence intervals (95% CI) were calculated, adjusting for predefined covariates.Results Of 2,696 women, 1,947 were black (1,014 in the preimplementation period and 933 in the postimplementation period) and 749 were nonblack (370 in the preimplementation period and 379 in the postimplementation period). Regardless of race, women in the postimplementation period had lower rates of SSI compared with those in the preimplementation period (black: 2.9 vs. 5.2%, aOR: 0.53 [95% CI: 0.33–0.85]; nonblack: 1.1 vs. 3.5%, aOR: 0.28 [95% CI: 0.09–0.89]). There was no interaction by race (p for interaction = 0.94).Conclusion The care bundle decreased SSI in both black and nonblack women but did not reduce racial disparities.
Keywords: care bundle; cesarean delivery; racial disparities; surgical site infections